2018
DOI: 10.1128/aac.01514-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incubation Temperature on Antibiotic Resistance and Virulence Factors of Acinetobacter baumannii ATCC 17978

Abstract: is a notorious opportunistic pathogen that is prevalent mainly in hospital settings. The ability of to adapt and to survive in a range of environments has been a key factor for its persistence and success as an opportunistic pathogen. In this study, we investigated the effect of temperature on the clinically relevant phenotypes displayed by at 37°C and 28°C. Surface-associated motility was significantly reduced at 28°C, while biofilm formation on plastic surfaces was increased at 28°C. Decreased susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…40 A report demonstrated that A. baumannii strains formed biofilm better at 30°C than at 37°C while another showed that biofilm formation on plastic surfaces was high at 28°C due to the up-regulation of certain biofilm-associated proteins (Baps) such as Csu and iron-uptake proteins in A. baumannii . 39 …”
Section: Temperaturementioning
confidence: 99%
“…40 A report demonstrated that A. baumannii strains formed biofilm better at 30°C than at 37°C while another showed that biofilm formation on plastic surfaces was high at 28°C due to the up-regulation of certain biofilm-associated proteins (Baps) such as Csu and iron-uptake proteins in A. baumannii . 39 …”
Section: Temperaturementioning
confidence: 99%
“…A. baumannii is by now suggested to be responsible for 2%–10% of all nosocomial infections worldwide (Antunes et al ., ; De Silva et al ., ; Wong et al ., ; Harding et al ., ). Primarily patients in intensive care units (ICUs) suffer from the opportunistic pathogen, which can cause, amongst others, pneumonia, sepsis, meningitis and infections of the urinary tract or wounds (Allen and Green, ; Dijkshoorn et al ., ; Peleg et al ., ; Howard et al ., ; McConnell et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential increase in PNAG production by the a/e2 mutant, it was not surprising to observe that the ∆a/e2 mutant developed a rdar-like morphotype on CR plates under conditions typically unfavorable to biofilm formation ( Fig. 3C) (37°C, unpublished data and (De Silva et al, 2018)). Complementation of the ∆a/e2 mutant restored the WT phenotype, confirming the role of gna-gne2 in biofilm formation.…”
Section: Gna-gne2 Are Required For Capsule Production Biofilm Formatmentioning
confidence: 95%